Diagnostic and Prognostic Value of Bone Marrow Morphology in Multiple Myeloma: A Cross-Sectional Analysis - Dr. Fatima Nizami, Dr MH Shariff, Dr Rajesh Krishna (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Multiple myeloma (MM) is a malignant plasma-cell disorder characterized byclonal proliferation within the bone marrow, resulting in anemia, renal impairment,hypercalcemia, and bone destruction